1975
DOI: 10.1021/jm00241a014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of some antitumor benzophenanthridinium salts

Abstract: A facil synthesis of benzophenanthridinium salts has been developed and used for preparing a number of these compounds. The antitumor activities in mouse leukemia L1210 (LE) and P388 (PS) were determined as well as some selected antimicrobial activities. Although antitumor activity was exhibited by several of the derivatives, none was as active as the naturally occurring alkaloid fagaronine. Fagaronine was made available as a synthetic by an improved procedure. Some structure-activity relationships among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 3 publications
0
38
0
1
Order By: Relevance
“…Other synthetic routes to 1 have been described by Ishii et al, [9] Treus et al, [4] Lunch et al, [5] and Š midrkal [10] , the latter being only a slight variation on the synthetic sequence reported by Gillespie et al [8] . Messmer et al [7] demonstrated the pronounced in vivo antileukemia activity of 1, which was then verified by Stermitz et al [11] and in preclinical studies at the National Cancer Institute [12] . The pharmacological and toxicological effects of 1 and other alkaloids in this group have since been tested in many investigations.…”
mentioning
confidence: 88%
“…Other synthetic routes to 1 have been described by Ishii et al, [9] Treus et al, [4] Lunch et al, [5] and Š midrkal [10] , the latter being only a slight variation on the synthetic sequence reported by Gillespie et al [8] . Messmer et al [7] demonstrated the pronounced in vivo antileukemia activity of 1, which was then verified by Stermitz et al [11] and in preclinical studies at the National Cancer Institute [12] . The pharmacological and toxicological effects of 1 and other alkaloids in this group have since been tested in many investigations.…”
mentioning
confidence: 88%
“…Boc-1,7-diaminoheptane (15). 37 The general procedure provided the desired compound as a colorless semisolid (0.473 g, 90%). 1 …”
Section: General Procedures For the Preparation Of Mono-boc-protected mentioning
confidence: 99%
“…f. et Thoms., Macleaya and Bocconia species from the Papaveraceae family, and some members of Zanthoxylum (Rutaceae). Although the QBAs are a relatively small class of plant products, they have attracted much attention from researchers because of their bioactivities: anti-inflammatory (Lenfeld et al, 1981), antimicrobial (Mitscher et al, 1978;Navarro, Villarreal, Rojas, & Lozoya, 1996;Odebiyi & Sofowora, 1979), antitumour (Nakanishi, Suzuki, Mashiba, Ishikawa, & Yokotsuka, 1998;Stermitz, Larson, & Kim, 1973;Stermitz et al, 1975;Tin-Wa, Bell, Bevelle, Fong, & Farnsworth, 1974;Zee-Cheng & Cheng, 1975), antiviral (Sethi, 1979), cytotoxic (Cordell & Farnsworth, 1976) and anti-liver mitochondrial monoamine oxidase (Iagodina, Nikol'skaia, & Faddeeva, 2003). With respect to the antimicrobial activities of QBAs, previous research has mainly focused on the total alkaloids containing QBAs from the plant, while only a few studies on 1 and 2 have been reported.…”
Section: Introductionmentioning
confidence: 99%